Catechin Nanoemulsion Serum Formulation as Anti Aging - Sintia, Ulma; Hasibuan, Elmi Sariani (LLDIKTI Wilayah 1, 2023)
Catechins very potential as active ingredients to be formulated in cosmetic preparations because catechins have antioxidant activity and effective as anti-aging. The effect and confortness of using catechins on the skin is enhanced through nanoemulsian serum formulation. Nanoemulsion are stable, transparent and has a very small droplet size usually in the range of 20-500 nm. This study aims to formulate a nanoemulsion preparation of the active compound catechin and evaluate its effect as anti-aging. Catechins were formulated in nanoemulsion serum preparations with various concentrations (1%, 2%, and 3%). Effectiveness testing was conducted for 21 consecutive days on 4 volunteers. The results showed that the use of catechin nanoemulsion serum formula 2 with a globule size of 46 nm from the composition of catechin 2%, lecithin 2.5%, olive oil 1%, and Tween 80 35% effectively enhanced skin conditions related to signs of aging such as wrinkles, dark spots, skin tone, and pores.